Plan quinquenal de marketing para la empresa Okinawaserv Cia. Ltda. del cantón Lago Agrio, provincia de Sucumbíos. - Wong Andrade, Víctor Julio (2016)
Research on the proposal for a quiquennial marketing plan for the company Okinawaserv Cia. Ltda., Was developed in the Lago Agrio Canton Province of Sucumbíos, with the general objective to develop a marketing plan in order to improve the economic and competitive development of the company as a strategic marketing plan is an essential tool in all organization, it facilitates effective marketing of any product or service. It is very risky to try a business succeed without having developed a strategic marketing plan. Following an appropriate methodological procedure within a marketing plan and drawn in schema regulated institutionally, my research was developed as follows: In the first instance there has been an external analysis of the factors involved in the company, such as economic, social, political, technological, the same that allowed identify threats and opportunities affecting the company, which were weighted priority. They have determined that the company does not take advantage of external opportunities and susceptible to threats from their environment more than that is weak internally. Internal company analysis was conducted by applying surveys to internal and external customers; as well as an interview with the manager of the company, which allowed determine the strengths and weaknesses of the company, the same as they were weighted according to importance, which determined that the company is not using its strengths to enable it to correct its weaknesses. By internal analysis of the company, the company diagnosis was made OKINAWASERV CIA. LTDA. under current conditions it encounters. Subsequently it has made the high-impact matrix, which allowed to consider strategic to be developed in the final proposal objectives. The proposal has been determined that the lack of a defined vision and mission for the company, has created this does not have a clear direction. It has determined the vision and mission of the company OKINAWASERV CIA. LTDA., Which will help guide the fate of the company. The company OKINAWASERV CIA. LTDA., Lacks a marketing plan. The marketing plan to be implemented in this project is to select and perform the respective contracts with the media with the largest circulation, propose a training plan, improve customer service and promote the services offered by the company OKINAWASERV CIA. LTDA.